2011
DOI: 10.1371/journal.pone.0028592
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Deterioration in Health Related Quality of Life as Predictor for Survival in Patients with Glioblastoma: A Prospective Study

Abstract: BackgroundStudies indicate that acquired deficits negatively affect patients' self-reported health related quality of life (HRQOL) and survival, but the impact of HRQOL deterioration after surgery on survival has not been explored.ObjectiveAssess if change in HRQOL after surgery is a predictor for survival in patients with glioblastoma.MethodsSixty-one patients with glioblastoma were included. The majority of patients (n = 56, 91.8%) were operated using a neuronavigation system which utilizes 3D preoperative M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
42
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 37 publications
5
42
2
3
Order By: Relevance
“…We have previously demonstrated that early deterioration in HRQoL following surgery is independently and markedly associated with impaired survival, 16 and the same tendencies are seen in the present study. The rapid decline seen in some patients is seemingly not always due to perioperative complications, surgically induced deficits, or suboptimal extents of resection.…”
Section: Association Between Early Deterioration In Hrqol and Short Ssupporting
confidence: 90%
See 2 more Smart Citations
“…We have previously demonstrated that early deterioration in HRQoL following surgery is independently and markedly associated with impaired survival, 16 and the same tendencies are seen in the present study. The rapid decline seen in some patients is seemingly not always due to perioperative complications, surgically induced deficits, or suboptimal extents of resection.…”
Section: Association Between Early Deterioration In Hrqol and Short Ssupporting
confidence: 90%
“…By including even short-term HRQoL dynamics (e.g., the time before surgery to end of radiotherapy) rather than a single static measure, more precise information may be achieved since early changes in HRQoL may reflect the aggressiveness of the disease. This was suggested by our previous study, 16 and is confirmed in this study, where patients with early progressive deterioration after surgery had a substantially shorter survival. This is further supported by Bosma et al 3 who compared HRQoL in short-term and long-term survivors and found a deterioration in HRQoL in short-term survivals between baseline (after surgery, before radiotherapy) and 4 month follow-up, whereas the long-term survivors experienced improved HRQoL.…”
Section: Association Between Early Deterioration In Hrqol and Short Ssupporting
confidence: 89%
See 1 more Smart Citation
“…It has been well shown that adverse events are typically higher in randomized controlled trials (RCTs), where specific efforts are made to document outcomes, than in retrospective case series. 3,6 This study demonstrates the unreliability of such retrospective reviews and calls for validated measures of neurosurgical morbidity.…”
mentioning
confidence: 90%
“…Patient-reported outcomes at specified time points could be another step toward reducing assessment bias and emphasizing outcomes that are relevant to the patients themselves. 6,12 Assessing quality of life or quality of survival in brain operations that are essentially palliative in nature may, for example, be more relevant than extent of resection. Still, patient-reported outcomes are more demanding and call for standardized follow-up of patients instead of retrospective review of medical records.…”
mentioning
confidence: 99%